Penetapan Harga Jual dengan Metode Cost Plus Pricing Menggunakan Pendekatan Full Costing Pada UD. Dzaky Alam Food Tahun 2019 - Sigit Wisnu Setya Bhirawa; Lailatul Fitriah (POLITEKNIK CAHAYA SURYA, 2020)
Each company generally aims to earn profits, especially manufacturing companies, and this profit is obtained from sales activities and the company can compete in the market. For this reason, the calculation of the cost of goods manufactured in determining the selling price of the product is very important because if the company does not calculate the cost of goods manufactured correctly, the company will experience problems in determining the selling price. The purpose of this study is to analyze the calculation of the cost of goods manufactured using the full costing method and the calculation of the selling price using the cost plus pricing method and whether the calculation of the cost of goods manufactured affects the determination of the selling price. The method used in this research is quantitative descriptive analysis. The results of this study indicate that the calculation of the cost of goods manufactured using the full costing method and the calculation of the selling price using the cost plus pricing method obtained different results, namely lower than the company's calculations. The lower the cost of goods manufactured, the lower the selling price. It is hoped that the company will apply the cost plus pricing method with a full costing approach in determining the selling price, because it is felt that this method is more appropriate than the method used by the previous company so that the company can compete in the market and can develop more.Keywords: Cost of Production, Selling Price, Full Costing, Cost Plus Pricing.